The characteristic expression of circulating MicroRNAs in osteoporosis: a systematic review and meta-analysis - Gao, Jie; Zhang, Xiuzhen; Ding, Jing; Zhang, Houli; Zhang, Xu; Jiang, Juan; Chen, Wenwen (Frontiers in Endocrinology, 2024)
Objective To evaluate the characteristics of the circulating microRNA expression profiles in patients with osteoporosis. Methods A systematic literature search was performed using the Web of Science, PubMed, Embase, Cochrane Library, China National Knowledge Infrastructure (CNKI), VIP, and WANFANG databases from inception until 1 March 2024. The search strategy employed keywords, encompassing “osteoporosis”, “bone loss”, or “osteopenia” and “miRNA” or “microRNA”. The Newcastle-Ottawa Scale (NOS) quality assessment scale was used to evaluate the methodological quality. Heterogeneity tests and statistical analyses of all data were performed by Stata 16.0. The differences in microRNA levels between groups were illustrated by the weighted mean difference (WMD) and 95% confidence interval (95% CI). Results A total of 27 studies were included and analyzed in the meta-analysis, with 2,263 participants. The results showed that miR-21-5p (WMD 0.88, 95% CI: 0.22 to 1.55), miR-125b-5p (WMD 6.63, 95% CI: 0.19 to 13.08), miR-483-5p(WMD 6.43, 95% CI: 3.26 to 9.61), miR-133a (WMD 1.43, 95% CI: 1.39 to 1.47), miR-422a (WMD 1, 95% CI: 0.28 to 1.72), and miR-214-3p (WMD 2.03, 95% CI: 0.14 to 3.92) were significantly upregulated, and miR-497-5p (WMD -0.57, 95% CI: -0.98 to -0.17) was significantly downregulated. Conclusion miR-21-5p, miR-125b-5p, miR-483-5p, miR-133a, miR-497-5p, miR-422a, and miR-214-3p might serve as potential diagnostic biomarkers for osteoporosis. In the future, integrating these miRNAs to build a diagnostic model might be a promising diagnosis strategy for osteoporosis. Systematic review registration https://www.crd.york.ac.uk/PROSPERO/, identifier CRD42023481209.